Exercise training improves characteristics of exercise oscillatory ventilation in chronic heart failure. (May 2017) - Panagopoulou, Niki; Karatzanos, Eleftherios; Dimopoulos, Stavros; Tasoulis, Athanasios; Tachliabouris, Ioannis; Vakrou, Styliani; Sideris, Antonios; Gratziou, Christina; Nanas, Serafim
Background: Exercise oscillatory ventilation in chronic heart failure has been suggested as a factor related to adverse cardiac events, aggravated prognosis and higher mortality. Exercise training is well known to affect exercise capacity and mechanisms of pathophysiology beneficially in chronic heart failure. Little is known, however, about the exercise training effects on characteristics of exercise oscillatory ventilation in chronic heart failure patients. Design and methods: Twenty (out of 38) stable chronic heart failure patients exhibited exercise oscillatory ventilation (age 54 ± 11 years, peak oxygen uptake 15.0 ± 5.0 ml/kg per minute). Patients attended 36 sessions of high intensity interval exercise. All patients underwent cardiopulmonary exercise testing before and after the programme. Assessment of exercise oscillatory ventilation was based on the amplitude of cyclic fluctuations in breathing during rest and exercise. All values are mean ± SD. Results: Exercise training reduced ( P  < 0.05) the percentage of exercise oscillatory ventilation duration (79.0 ± 13.0 to 50.0 ± 25.0%), while average amplitude (5.2 ± 2.0 to 4.9 ± 1.6 L/minute) and length (44.0 ± 10.9 to 41.0 ± 6.7 seconds) did not change ( P  > 0.05). Exercise oscillatory ventilation patients also increased exercise capacity ( P  < 0.05). Conclusions: A rehabilitation programme based on high intensity interval training improved exercise oscillatory ventilation observed in chronic heart failure patients, as well as cardiopulmonary efficiency and functional capacity.